2013
DOI: 10.1155/2013/580968
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon at the Interface of Antiviral Immunity and Immune Regulation: The Curious Case of HIV-1

Abstract: Type I interferon (IFN-I) play a critical role in the innate immune response against viral infections. They actively participate in antiviral immunity by inducing molecular mechanisms of viral restriction and by limiting the spread of the infection, but they also orchestrate the initial phases of the adaptive immune response and influence the quality of T cell immunity. During infection with the human immunodeficiency virus type 1 (HIV-1), the production of and response to IFN-I may be severely altered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 310 publications
(355 reference statements)
0
17
0
1
Order By: Relevance
“…Type I IFN induces an array of proteins that interfere with virus replication in order to restrict and limit viral spread from cell to cell [5, 6]. 2’–5’-oligoadenylate synthetase (OAS) is an enzyme induced by Type I IFN that activates latent nuclease RNaseL which then mediates viral RNA degradation.…”
Section: Type I Interferons: Interferon- Alpha/beta (Ifn-α/β)mentioning
confidence: 99%
See 1 more Smart Citation
“…Type I IFN induces an array of proteins that interfere with virus replication in order to restrict and limit viral spread from cell to cell [5, 6]. 2’–5’-oligoadenylate synthetase (OAS) is an enzyme induced by Type I IFN that activates latent nuclease RNaseL which then mediates viral RNA degradation.…”
Section: Type I Interferons: Interferon- Alpha/beta (Ifn-α/β)mentioning
confidence: 99%
“…However, complete elimination of intracellular infection by pathogens requires activation of the adaptive immune response and the Type I IFNs have an active role in this activation process. Type I IFNs promote the maturation of dendritic cells (DCs) that facilitate CD4 + T cell differentiation into either Th1 or Th2 cells [5, 6]. Studies have shown that Type I IFN experienced APCs are capable of cross-presentation and stimulate naïve CD8 + T cells, resulting in clonal expansion and proliferation.…”
Section: Type I Interferons: Interferon- Alpha/beta (Ifn-α/β)mentioning
confidence: 99%
“…There are two types of IFNs: Type I and Type II [2]. Type I IFNs are produced in large quantities in response to viral infections, and they are generally regarded as a key bridging mechanism between the innate and adaptive immune responses, exerting antiviral activity and immune-stimulatory functions, such as promoting antigen-presenting cell maturation and modulating T helper cell responses [3][4][5][6][7]. Canonical type I IFNs activate the Janus kinase (JAK) signal transducer and activator of transcription (STAT) pathway, leading to the transcription of IFN-stimulated genes (ISGs), such as myxovirus-resistance protein, oligoadenylate synthetase, and protein kinase [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Eradication of HCV infection involves coordinated effort between innate and adoptive immunity, as the innate immune responses initially, and later adaptive immunity becomes operational 8 weeks post‐infection . Initially, innate immunity recognises HCV via pattern recognition receptors (PRR) through TLRs, which target pathogen‐associated molecular patterns (PAMPs) found on HCV, thus augmenting immunity through upregulating IFN secretion and induction of IFN‐α‐inducible genes involved in antiviral and immune regulatory functions. The association of TLR with virological response to peg‐IFN plus RBV therapy in HCV‐infected patients explains the appearance of TLR4 and TLR2 as the top 10 treatment response related genes (Table ).…”
Section: Discussionmentioning
confidence: 99%